Buddlejaceae endémicas del Perú - León, Blanca (2006)
The Buddlejaceae are represented in Peru by two genera and 16 species (Norman, 2000; Ulloa Ulloa et al., 2004), mainly shrubs. Here we recognize two endemic species, both in the genus Buddleja. These endemic taxa are found in Mesoandean, Humid and Dry Puna, and Paramo regions, between 2650 and 3900 m elevation. One species has been registered within the Peruvian parks system.